Theoretical Investigation of the CO2 Capture Properties of γ-LiAlO2 and α-Li5AlO4 - Duan, Yuhua (Micro and Nanosystems, 2021)
Aims: The aim is to develop effective CO2 sorbent materials for fighting global climate change. Background: CO2 is one of the major combustion products which once released into the air can contribute to global climate change. There is a critical need for the development of new materials that can capture CO2 reversibly with acceptable energy and cost performance for these applications. Accordingly, solid sorbents have been reported to be promising candidates for CO2 sorbent applications through a reversible chemical transformation due to their high CO2 absorption capacities at moderate working temperatures. Objective: To evaluate the CO2 capture performance of γ-LiAlO2 and α-Li5AlO4 in comparison with other solid sorbents. Methods: By combining first-principles density functional theory with phonon lattice dynamics calculations, the thermodynamic properties of the CO2 capture reaction by sorbent as a function of temperature and pressure can be determined without any experimental input beyond crystallographic structural information of the solid phases involved. The calculated thermodynamic properties are used to evaluate the equilibrium properties for the CO2 adsorption/desorption cycles. Results: Both γ-LiAlO2 and α-Li5AlO4 are insulators with wide band gaps of 4.70 and 4.76 eV, respectively. Their 1st valence bands just below the Fermi level are mainly formed by p orbitals of Li, O and Al as well as s orbital of Li. By increasing the temperature from 0 K up to 1500 K, their phonon free energies are decreased while their entropies are increased. The thermodynamic properties of CO2 capture reactions by γ-LiAlO2 and α-Li5AlO4 are calculated and used for comparing with other wellknown sorbent materials. Conclusion: The calculated thermodynamic properties of γ-LiAlO2 and α-Li5AlO4 reacting with CO2 indicate that LiAlO2 could be used for capturing CO2 at warm temperature range (500-800 K) while α- Li5AlO4 could be used for capturing CO2 at high-temperature range (800-1000 K), which are in good agreement with available experimental data.
Keywords: solid sorbents